Nonlinear radiative and mixed convective flow of an Eyring-Powell fluid with Joule heating and entropy optimization - S. Naz; T. Hayat; S. Momani (Results in Engineering)
Here nonlinear mixed convective flow of magnetized Eyring-Powell fluid is addressed. Energy expression comprised of heat generation/absorption, Ohmic heating and dissipation. Formulation for nonlinear radiative flow is made. Convective conditions are deliberated for mass and heat transfer. Entropy optimized flow is organized. Aspect of Arrhenius activation energy is explored. Relevant problem is formulated into dimensionless ordinary differential system (ODEs). ND-Solve scheme is employed to develop numerical solution. Graphs are organized for liquid flow, entropy rate and temperature and concentration distributions. Numerical outcomes for surface drag force and Nusselt and Sherwood numbers regarding interesting quantities are studied. Higher Biot numbers augment concentration and temperature fields. Larger magnetic field decay liquid flow while opposite occurs for liquid parameter. An intensification in entropy holds for Brinkman number and magnetic effect. Concentration declines against reaction variable. Concentration augments through higher activation energy and solutal Biot parameter. Higher approximation of buoyancy ratio give rise to liquid flow whereas reverse situation occurs for surface drag force. Nusselt number for Eckert number and radiation has opposite impacts whereas Schmidt number and activation energy enhance for Sherwood number.